Integration of Neuroscience into Early Childhood Educational Psychology: A Critical Literature Review of Cognition, Emotion, and Pedagogical Implications - Hani Hasnah Safitri; Ulul Albab; Siti Mumun Muniroh; Mohammad Adam; Faiz Akhmad Khan (Journal of Early Childhood Education Perspectives, 2026)
The integration of neuroscience into early childhood educational psychology has gained increasing scholarly attention in response to the need for a holistic and evidence-based understanding of young children’s learning and development. This article aims to critically analyze the contribution of neuroscience in enriching the theoretical framework of early childhood educational psychology, particularly in understanding the interrelationship between cognition, emotion, and pedagogical implications in early learning contexts. Employing a critical literature review approach, this study examines articles from reputable international and accredited national journals related to educational neuroscience, early childhood education, and educational psychology. The analysis is conducted through a reflective thematic synthesis that places neuroscientific findings in dialogical engagement with contemporary educational theory. The findings indicate that neuroscience functions as an epistemic lens that deepens understanding of early childhood learning processes, rather than as a direct methodological prescription for classroom practice. This article emphasizes the importance of critical awareness of neuromyths and highlights neuroscience as a foundation for early childhood educators’ professional reflection in designing developmentally appropriate, ethical, and meaningful learning experiences. Theoretically, this study contributes to an integrative framework for early childhood educational psychology, while practically offering reflective direction for educators and researchers in engaging with neuroscience critically and responsibly.